Revising the “Hype Pipeline” Model in Scientific Communication - Taschner, Natalia Pasternak; de Almeida, Luiz Gustavo; Orsi, Carlos (Frontiers in Communication, 2021)
Scientific hype understood as an exaggeration of the significance and/or promise of scientific discovery, has been often seen as a problem for the production of science communication, not of reception; press releases and traditional media are usually blamed for exaggerating claims and using click-bait headlines, and the interest of the public is usually seen as the background motivator behind the hype. The role of social media in the present COVID-19 crisis, however – specially the sudden ascension to fame of hydroxychloroquine as a purported “game-changer” in the pandemic – challenges us to change this perception. We propose that we need a new model in science communication, where hype can come directly from the public, and not just as a product of media sensationalism